2014
DOI: 10.1021/jp5052479
|View full text |Cite
|
Sign up to set email alerts
|

Methane Clathrate Hydrate Nucleation Mechanism by Advanced Molecular Simulations

Abstract: The nucleation mechanisms of methane hydrates are studied using welltempered metadynamics and restrained molecular dynamics. The collective variables we used to follow the process are the methane−methane and methane−water coordination numbers, from which we computed the corresponding Landau free energy surface. This surface is characterized by two minima, corresponding to the two-phase methane bubble/ water solution and clathrate crystal, and a transition state. The clathrate crystal is of type II, while in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
74
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 93 publications
(87 citation statements)
references
References 54 publications
8
74
4
Order By: Relevance
“…What sets these systems apart is that different subdomains can have different pressures. A broad range of phenomena falls into this class, including homogeneous and heterogeneous vapor nucleation, [6][7][8][9][10][11][12] nucleation of polymorphic crystals, [13][14][15][16] dissolution of bubbles and droplets, and condensation or evaporation. In this work we show that in such cases, in which the relative amount of the two phases changes along the process, the pressure of the preexisting bulk metastable phase might change during the process when one uses global barostats, which is different from the condition at which experiments are carried out.…”
Section: Introductionmentioning
confidence: 99%
“…What sets these systems apart is that different subdomains can have different pressures. A broad range of phenomena falls into this class, including homogeneous and heterogeneous vapor nucleation, [6][7][8][9][10][11][12] nucleation of polymorphic crystals, [13][14][15][16] dissolution of bubbles and droplets, and condensation or evaporation. In this work we show that in such cases, in which the relative amount of the two phases changes along the process, the pressure of the preexisting bulk metastable phase might change during the process when one uses global barostats, which is different from the condition at which experiments are carried out.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21] Theoretically, the nucleation and growth process of methane hydrate have been simulated and explored on the atomic and molecular level through molecular dynamics simulations. [23][24][25][26][27][28][29][30] The interaction between host water cages and guest molecules, 32,41 stability, diffusion and vibrations of guest molecules in water cavities of clathrate hydrates, 31,34,[38][39][40][42][43] and phase transition between ice and methane clathrates have been studied by firstprinciple calculations. 37,44 Experimentally, Raman spectra of hydrocarbon hydrates have demonstrated that the CH stretching frequency of the guest molecule is commonly (but not always) lower when in a large cage than when in a small cage [13][14][15] .…”
Section: Introductionmentioning
confidence: 99%
“…1,2 A unit cell in sII hydrate consists of 136 water molecules forming sixteen small 5 12 cages and eight large hexadecahedral 5 12 6 4 cages. 1,2 In recent years, the molecular simulation of clathrate hydrates has revealed much about their structural properties, 3 and Monte Carlo 4 and molecular dynamics (MD) simulations, whether brute force (i.e., standard) [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] or biased, [22][23][24][25] of hydrate formation have revealed a propensity for either (approximately) sI or sII polymorphs to form, despite one form typically being most thermodynamically stable for a given guest type (and temperature/pressure). Given that such simulation can provide molecular-level insights into hydrate-formation dynamics, this allows for probing the structural nature of the growing hydrate a) Authors to whom correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%